Phylodynamic analysis of foot-and-mouth disease virus evolution in Mar Chiquita, Argentina - Laura C. Lozano Calderón; Gustavo S. Cabanne; Andrea Marcos; Sabrina Galdo Novo; Carolina Torres; Andrés M. Perez; Oliver G. Pybus; Guido A. König (Archives of Virology, 2024)

Seasonal dynamics of the wild rodent faecal virome - Jayna Raghwani; Christina L. Faust; Sarah François; Dung Nguyen; Kirsty Marsh; Aura Raulo; Sarah C. Hill; Kris V. Parag; Peter Simmonds; Sarah C. L. Knowles; Oliver G. Pybus (Molecular Ecology, 2023)
Viral discovery studies in wild animals often rely on cross‐sectional surveys at a single time point. As a result, our understanding of the temporal stability of wild animal viromes remains poorly resolved. While studies of single host–virus systems indicate that host and environmental factors influence seasonal virus transmission dynamics, comparable insights for whole viral communities in multiple hosts are lacking. Utilizing noninvasive faecal samples from a long‐term wild rodent study, we characterized viral communities of three common European rodent species ( Apodemus sylvaticus , A. flavicollis and Myodes glareolus ) living in temperate woodland over a single year. Our findings indicate that a substantial fraction of the rodent virome is seasonally transient and associated with vertebrate or bacteria hosts. Further analyses of one of the most common virus families, Picornaviridae, show pronounced temporal changes in viral richness and evenness, which were associated with concurrent and up to ~3‐month lags in host density, ambient temperature, rainfall and humidity, suggesting complex feedbacks from the host and environmental factors on virus transmission and shedding in seasonal habitats. Overall, this study emphasizes the importance of understanding the seasonal dynamics of wild animal viromes in order to better predict and mitigate zoonotic risks.

Phylodynamics of H5N1 avian influenza virus in Indonesia - TOMMY TSAN‐YUK LAM; CHUNG‐CHAU HON; PHILIPPE LEMEY; OLIVER G. PYBUS; MANG SHI; HEIN MIN TUN; JUN LI; JINGWEI JIANG; EDWARD C. HOLMES; FREDERICK CHI‐CHING LEUNG (Molecular Ecology, 2012)
Understanding how pathogens invade and become established in novel host populations is central to the ecology and evolution of infectious disease. Influenza viruses provide unique opportunities to study these processes in nature because of their rapid evolution, extensive surveillance, large data sets and propensity to jump species boundaries. H5N1 highly pathogenic avian influenza virus (HPAIV) is a major animal pathogen and public health threat. The virus is of particular importance in Indonesia, causing severe outbreaks among poultry and sporadic human infections since 2003. However, little is known about how H5N1 HPAIV emerged and established in Indonesia. To address these questions, we analysed Indonesian H5N1 HPAIV gene sequences isolated during 2003–2007. We find that the virus originated from a single introduction into East Java between November 2002 and October 2003. This invasion was characterized by an initially rapid burst of viral genetic diversity followed by a steady rate of lineage replacement and the maintenance of genetic diversity. Several antigenic sites in the haemagglutinin gene were subject to positive selection during the early phase, suggesting that host‐immune‐driven selection played a role in host adaptation and expansion. Phylogeographic analyses show that after the initial invasion of H5N1, genetic variants moved both eastwards and westwards across Java, possibly involving long‐distance transportation by humans. The phylodynamics we uncover share similarities with other recently studied viral invasions, thereby shedding light on the ecological and evolutionary processes that determine disease emergence in a new geographical region.

Mitogenetic structure of brown bears ( Ursus arctos L.) in northeastern Europe and a new time frame for the formation of European brown bear lineages - URMAS SAARMA; SIMON Y. W. HO; OLIVER G. PYBUS; MARJU KALJUSTE; IGOR L. TUMANOV; ILPO. KOJOLA; ALEX A. VOROBIEV; NIKOLAI I. MARKOV; ALEXANDER P. SAVELJEV; HARRI VALDMANN; ELENA A. LYAPUNOVA; ALEXEI V. ABRAMOV; et al. (Molecular Ecology, 2007)
We estimated the phylogenetic relationships of brown bear maternal haplotypes from countries of northeastern Europe (Estonia, Finland and European Russia), using sequences of mitochondrial DNA (mtDNA) control region of 231 bears. Twenty‐five mtDNA haplotypes were identified. The brown bear population in northeastern Europe can be divided into three haplogroups: one with bears from all three countries, one with bears from Finland and Russia, and the third composed almost exclusively of bears from European Russia. Four haplotypes from Finland and European Russia matched exactly with haplotypes from Slovakia, suggesting the significance of the current territory of Slovakia in ancient demographic processes of brown bears. Based on the results of this study and those from the recent literature, we hypothesize that the West Carpathian Mountains have served either as one of the northernmost refuge areas or as an important movement corridor for brown bears of the Eastern lineage towards northern Europe during or after the last ice age. Bayesian analyses were performed to investigate the temporal framework of brown bear lineages in Europe. The molecular clock was calibrated using Beringian brown bear sequences derived from radiocarbon‐dated ancient samples, and the estimated mutation rate was 29.8% (13.3%−47.6%) per million years. The whole European population and Western and Eastern lineages formed about 175 000, 70 000 and 25 000 years before present, respectively. Our approach to estimating the time frame of brown bear evolution demonstrates the importance of using an appropriate mutation rate, and this has implications for other studies of Pleistocene populations.

Rates of Molecular Evolution in RNA Viruses: A Quantitative Phylogenetic Analysis - Gareth M. Jenkins; Andrew Rambaut; Oliver G. Pybus; Edward C. Holmes (Journal of Molecular Evolution, 2002)